2015
DOI: 10.2147/ijn.s76104
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles enhance the anticancer activity of cathelicidin LL-37 peptide against colon cancer cells

Abstract: The pleiotropic activity of human cathelicidin LL-37 peptide includes an ability to suppress development of colon cancer cells. We hypothesized that the anticancer activity of LL-37 would improve when attached to the surface of magnetic nanoparticles (MNPs). Using colon cancer culture (DLD-1 cells and HT-29 cells), we evaluated the effects of MNPs, LL-37 peptide, its synthetic analog ceragenin CSA-13, and two novel nanosystems, ie, MNP@LL-37 and MNP@CSA-13, on cancer cell viability and apoptosis. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
(43 reference statements)
4
47
0
Order By: Relevance
“…Our study clearly indicates that ceragenin CSA-13, apart from its pleiotropic antimicrobial properties48495051, possesses great potential for development of a new sporicidal agent. However, additional studies are needed to determine the exact mechanism of action involved in the activity of this compound against B. subtilis spores.…”
Section: Discussionmentioning
confidence: 63%
“…Our study clearly indicates that ceragenin CSA-13, apart from its pleiotropic antimicrobial properties48495051, possesses great potential for development of a new sporicidal agent. However, additional studies are needed to determine the exact mechanism of action involved in the activity of this compound against B. subtilis spores.…”
Section: Discussionmentioning
confidence: 63%
“…For instance, theranostics and drug delivery strategies using magnetic anti-cancer drugs are expected to bring new hope for cancer therapy [40]. Indeed, Niemirowicz et al reported that magnetic nanoparticles enhance the anticancer activity of LL-37 against colon cancer cells [41]. Moreover, using mesoporous silica nanoparticles has been investigated [42].…”
Section: Discussionmentioning
confidence: 99%
“…For eons, antimicrobial peptides (AMPs) have played a central role in innate immunity against bacteria, fungi and lipid enveloped viruses [5][6][7][8][9]. The diversity of their primary sequences suggests independent evolution, and despite their ubiquity, bacteria generally remain susceptible to AMPs.…”
Section: Introductionmentioning
confidence: 99%